Correlation of glomerular filtration rate and fibroblast growth factor-23 levels in chronic kidney disease; sub analysis chronic kidney disease-mineral and bone disorder study - Akiko Syawalidhany Tahir; Haerani Rasyid; Syakib Bakri; Hasyim Kasim; Tutik Harjianti; Muhammad Luthfi Parewangi; Harun Iskandar; Arifin Seweng (Society of Diabetic Nephropathy Prevention, 2024)
Introduction: One of the chronic kidney disease (CKD) manifestations is mineral disorder, such as phosphate and calcium. Phosphatonin levels are regulated by the hormone phosphatonin, which the most commonly associated with CKD is fibroblast growth factor-23 (FGF-23), mainly synthesized by bone cells. The increase in FGF-23 in CKD subjects is a physiological response to stabilize phosphate levels. Several conditions can increase FGF-23 levels including age, body mass index (BMI), diabetes mellitus (DM), and hypertension. Objectives: This study aims to test the correlation between FGF-23 levels at various stages of glomerular filtration rate (GFR) in CKD. Patients and Methods: This study is observational with a cross-sectional approach conducted at Wahidin Sudirohusodo and Unhas hospitals of Makassar. Subjects are CKD patients which meet inclusion criteria. Intact serum FGF-23 levels were measured using an ELISA (enzyme-linked immunosorbent assay) kit (Immutopics). Statistical analysis was conducted using ANOVA test, Mann-Whitney U, and Spearman's correlation tests. Statistical results are considered significant if P<0.05. Results: The research was conducted on 78 subjects with CKD stages 3, 4 and 5, which consisted of 40 men and 38 women. The correlation test showed that the lower the GFR, the higher the FGF-23 level (P<0.05). No significant correlation between age, body mass index, diabetes mellitus, and hypertension with FGF-23 were detected (P>0.05). Conclusion: We found that every increase in the CKD stages and decrease of GFR, would be associated with an increase in the plasma levels of FGF-23. However, FGF-23 plasma concentration had no significant correlation with age, BMI, DM, and hypertension.